Eficacia de la luz pulsada intensa como tratameinto en ojo seco evaporativo asociado a la disfunción de las glándulas de meibomio: revisión Bibliográfica (2022)
Dry eye is characterized by a lubrication deficiency, causing alterations in the corneal and conjunctival surface, and may be associated with Meibomian Gland Dysfunction (MGD). Intense Pulsed Light (IPL) treatment is non-invasive and produces a thermal effect that has shown effective results, but further study is still required in its application and management. Objective: To describe the efficacy of IPL as a treatment for evaporative dry eye associated with Meibomian gland dysfunction based on a review of the literature. Methodology: Bibliographic review, in databases, Scielo, Pubmed, ScienceDirect, Dialnet of articles in English, Spanish, Portuguese and French, between the years 2015 and 2021.